Prognostic value of anemia in patients with ST-elevation myocardial infarction. (14th October 2021) - Costa, R; Frias, A; Campinas, A; Luz, A; Santos, M; Torres, S
Abstract: Introduction: Haemoglobin (Hb) levels are an important outcome predictor in several diseases. Purpose: We aimed to evaluate Hb at hospital admission in patients with ST-segment elevation myocardial infarction (STEMI) as a predictor of in-hospital complications, mortality and heart failure (HF) during follow-up. Methods: We retrospectively studied consecutive STEMI patients treated with primary percutaneous coronary intervention between January 2010 and December 2016. Clinical data was retrieved by review of patients' clinical records. Severity of anaemia was defined according World Health Organization cut-offs. Results: Of 864 patients with mean age of 63±13 years, 646 (75%) were male. Mean Hb at hospital admission was 14±2g/dL, 682 (81%) with normal Hb, 118 (14%) with mild anaemia, 45 (5%) with moderate anaemia and 2 (0.2%) with severe anaemia. Female gender, smoking, diabetes, hypertension, previous myocardial infarction and peripheral artery disease were associated to higher incidence of anaemia at hospital admission. Anaemia was also associated to Killip-Kimball (KK) class ≥II at hospital admission. They also had higher incidence of in-hospital stroke, advanced atrioventricular block, gastrointestinal bleeding and blood transfusion. In-hospital mortality was 9%, higher patients with anaemia (13% vs 7%, p=0.022). Median follow-up was 43 (26–66) months. All-cause mortality was 14%, higher in patients with anaemia (27% vs 11%, p<0.001, Log rank test p<0.001). In multivariate analysis, age (HR 1.1, 95% CI 1.0–1.1), diabetes (HR 1.9, 95% CI 1.1–3.4), left ventricular ejection fraction (LVEF) at discharge (if <50%, HR 3.4, 95% CI 1.6–7.2), and anaemia at admission (HR 1.8, 95% CI 1.0–3.2) were independent predictors of all-cause death during follow-up. Incidence of de novo HF, clinical worsening or hospitalization was 18%, higher in patients with anaemia (27% vs 17%, p=0.007, Log rank test p=0.007). In multivariate analysis, age (HR 1.1, 95% CI 1.0–1.1), KK class (if II, HR 2.1, 95% CI 1.3–3.5; if III, HR 4.0, 95% CI 1.8–8.9; if IV, HR 2.1, 95% CI 1.2–3.9), body mass index (if obese, HR 2.5, 95 CI 1.4–4.4) and LVEF at discharge (if <50%, HR 4.2, 95% CI 2.2–7.7), but not anaemia at admission (p=0.633) were independent predictors HF. Conclusion: In our contemporary cohort of STEMI patients, the presence of anaemia at hospital admission was not only associated to in-hospital complications, but also all-cause mortality during follow-up. Funding Acknowledgement: Type of funding sources: None.